2015
DOI: 10.1080/19393210.2015.1007396
|View full text |Cite
|
Sign up to set email alerts
|

Lead and cadmium in raw buffalo, cow and ewe milk from west Azerbaijan, Iran

Abstract: In this study, 300 raw buffalo, cow and ewe milk samples from five townships in west Azerbaijan, Iran, were analysed. Lead and cadmium were determined using atomic absorption spectrophotometry. Mean concentration of lead and cadmium in buffalo milk samples was 0.018 ± 0.001 and 0.003 ± 0.001 mg/kg, respectively. Mean concentration of lead and cadmium in cow milk samples was 0.007 ± 0.001 and 0.001 ± 0.001 mg/kg, respectively, and in ewe milk, these mean values were 0.010 ± 0.001 and 0.002 ± 0.001 mg/kg, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
4
6
3
Order By: Relevance
“…Tajkarimi et al (2008) sampled 14 milk factories in different provinces of Iran and they found lead mean residues of 2.4±1.4 µg/kg in Shoosh (Khuzestan), one order of magnitude lower than the values indicated here. Compared to other studies (Najarnezhad et al, 2015) carried out in the Northwest of this country (West Azerbaijan province), we have reported higher exposure (µg/kg, 47.0 Pb and 4.7 Cd vs. 7.0 and 10.0, respectively). Whereas both provinces are in the West of Iran, Khuzestan is closer to polluted areas and more exposed to dominant winds carrying pollution from zones related to oil or conflict.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Tajkarimi et al (2008) sampled 14 milk factories in different provinces of Iran and they found lead mean residues of 2.4±1.4 µg/kg in Shoosh (Khuzestan), one order of magnitude lower than the values indicated here. Compared to other studies (Najarnezhad et al, 2015) carried out in the Northwest of this country (West Azerbaijan province), we have reported higher exposure (µg/kg, 47.0 Pb and 4.7 Cd vs. 7.0 and 10.0, respectively). Whereas both provinces are in the West of Iran, Khuzestan is closer to polluted areas and more exposed to dominant winds carrying pollution from zones related to oil or conflict.…”
Section: Discussioncontrasting
confidence: 94%
“…Our results showed the values of lead in the cow milk samples were in agreement with those reported from Turkey (Simsek et al, 2000;Ayar et al, 2009), Croatia (Pavlovic et al, 2004;Bilandzic et al, 2011), and several times higher than those reported from India (Tripathi et al, 1999;Dhanalakshmi and Gawdaman, 2013), Thailand (Parkpian et al, 2003), Italy (Licata et al, 2004), South Africa (Ataro et al, 2008), Spain (Gonzalez-Montaña et al, 2012), Greece (Gougoulias et al, 2014), and Iran (Najarnezhad and Akbarabadi, 2013;Najarnezhad et al, 2015;Mostafidi et al, 2016). Although they are inferior, to those investigated in Italy (Coni et al, 1995;Caggiano et al, 2005;Anastasio et al, 2006), India (Swarup et al, 2005), Romania (Serdaru et al, 2001),…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In case of Pb (Arora et al, 2014;Farell et al, 2013;Shepherd et al, 2012), barium (Ba; Austin et al, 2013), calcein and oxytetracycline (Kierdorf et al, 2013), it has been shown that dentine can give a spatially-resolved record of exposure to these elements/compounds during tooth formation, whereby the concentration of the compound or element in question in the dentine reflects the degree of exposure to the compound or element while this section of the dentine was formed/mineralised. Consistent with this, the change from the Pb-rich mixed milk/grass diet of lambs to the Pb-poor seaweed diet of adult North Ronaldsay sheep (Anastasio et al, 2006;Antunovic et al, 2005;Bacon et al, 1996;Hansen et al, 2003a;Najarnezhad et al, 2015;Ródenas de la Rocha et al, 2009;Schiener et al, 2015) is visible in the bioimages of our study: The arrows in Fig. 2E point out changes in Pb intensities in the primary dentine, with arrows originating in the younger primary dentine where lower intensities were observed and pointing toward the higher intensities in older primary dentine.…”
Section: Origin Of Arsenic In Seaweed-eating Sheep's Teethsupporting
confidence: 87%
“…He found that lead concentrations in raw cow milks from nine districts and in imported butter, cheese, cream and milk from 15 countries were lower than allowable limits (37). Similarly, Najarnezhad reported that milk cadmium contents from West Azerbaijan Province, Iran, included 0.003 ±0.001 mg/kg for buffalo milks; 0.001 ±0.001 mg/kg for raw cow milks; and 0.002 ±0.001 mg/kg for raw ewe milks (15). A comparison of data reviewed from literatures is presented in Table 6.…”
Section: Discussionmentioning
confidence: 97%